Biodisponibilidade de ferro in vitro e in vivo de misturas de feijões caupi e batata doce biofortificados - Corrêa, Sarah Ramos (2017)
Food biofortification is an ally in the fight against micronutrient deficiency. In Brazil, staple crops are produced with higher levels of iron, zinc and vitamin A, but little is known about the bioavailability of these nutrients and their interactions. The aim of the study was to evaluate the interaction of vitamin A in the bioavailability of iron from mixtures of conventional rice with – biofortified cowpea beans and sweet potato with iron and carotenoids pro vitamin A, respectively, using in vitro and in vivo methods, as well as evaluate the gene expression of proteins involved in iron metabolism. The foods were cooked and dried at 60ºC. The nutritional composition, phytates, total phenolics, iron and zinc of food flours were analyzed. The combinations used in the experiment consisted of rice + cowpea added or not of sweet potatoes. In vitro bioavailability of cowpea bean Guariba (G), Aracê (A), Xique Xique (X) and Tumucumaque (T) was assessed by Caco-2 cells. In the biological assay nine experimental groups (n = 8) were tested: Rice + Cowpea BRS Guariba (G); Rice + Cowpea BRS Guariba + Sweet Potato (GB); Rice + Cowpea BRS Aracê (A); Rice + Cowpea BRS Aracê + Sweet Potato (AB); Rice + Cowpea BRS Xique Xique (X); Rice + Cowpea BRS Xique Xique + Sweet Potato (XB); Rice + Cowpea BRS Tumucumaque (T); Rice + Cowpea BRS Tumucumaque + Sweet Potato (TB); Control (Ferrous Sulfate). Only the BRS Xique Xique cowpea presented higher bioavailability of iron in vitro in the absence of sweet potato compared to the blend with the potato. The other groups added of sweet potato did not differ among themselves, as well as the groups without the potato, and one compared to the other. Bioavailability of iron in vivo was assessed by the depletion/repletion method (period of 35 days). Hemoglobin Gain (Hb Gain), Hemoglobin Regeneration Efficiency (HRE) and Relative Biological Value of HRE (RBV-HRE) were evaluated. The gene expression of the transferrin and ferritin proteins were evaluated by RT-PCR. The Hb gain of the experimental groups did not differ from the control (p=0.05). The test groups presented similar levels of HRE (p=0.05). The in vivo bioavailability was higher for the control group (p <0.05), while the potato groups did not differ (p=0.05). The only group that differed from its counterpart without sweet potato was XB (p <0.05). mRNA expression of ferritin did not differ between the test and control groups (p=0.05). In what it refers to mRNA expression of transferrin, in which there was difference between the test and control groups (p <0.05), except the group Xique Xique (p <0.05). The association of rice and beans to sweet potato rich in carotenoids, did not favor the gene expression of proteins involved in the metabolism of iron, as well as the bioavailability of this mineral.